Priming maize resistance by its neighbors: activating 1,4-benzoxazine-3-ones synthesis and defense gene expression to alleviate leaf disease - Ding, Xupo; Yang, Min; Huang, Huichuan; Chuan, Youcong; He, Xiahong; Li, Chengyun; Zhu, Youyong; Zhu, Shusheng (Frontiers in Plant Science, 2015)
Plant disease can be effectively suppressed in intercropping systems. Our previous study demonstrated that neighbouring maize plants can restrict the spread of soil-borne pathogens of pepper plants by secreting defence compounds into the soil. However, whether maize plant can receive benefits from its neighbouring pepper plants in an intercropping system is little attention. We examined the effects of maize roots treated with elicitors from the pepper pathogen Phytophthora capsici and pepper root exudates on the synthesis of 1,4-benzoxazine-3-ones (BXs), the expression of defence-related genes in maize, and their ability to alleviate the severity of southern corn leaf blight (SCLB) caused by Bipolaris maydis. We found that SCLB was significantly reduced after the above treatments. The contents of 1,4-benzoxazine-3-ones (BXs: DIBOA, DIMBOA, and MBOA) and the expression levels of BX synthesis and defence genes in maize roots and shoots were up-regulated. DIMBOA and MBOA effectively inhibited the mycelium growth of Bipolaris maydis at physiological concentrations in maize shoots. Further studies suggested that the defence related pathways or genes in maize roots and shoots were activated by elicitors from the P. capsici or pepper root exudates. In conclusion, maize increased the levels of BXs and defence gene expression both in roots and shoots after being triggered by root exudates and pathogen from neighbouring pepper plants, eventually enhancing its resistance.